The reality of work ethics in the context of some demographic variables at ibn sina hospital-annaba - Gacemi, Rim (Journal of Human Sciences, 2021)
This study aims to investigate about the reality of work ethics in the context of some demographic variables such as gender and professional seniority. And this is just an initial forward looking and a field survey in ibn sina hospital annaba. Through this study ,we attempt to answer some of the suggested questions.